2014
DOI: 10.1088/1742-6596/568/5/052001
|View full text |Cite
|
Sign up to set email alerts
|

Weak antilocalization in (111) thin films of a topological crystalline insulator SnTe

Abstract: We grew single-crystal thin films of a topological crystalline insulator (TCI) SnTe with a smooth surface at the atomic scale by molecular beam epitaxy (MBE). In the magnetoresistance (MR) measurement, we observed both positive and negative components near zero magnetic field at lowest temperatures of 2 -3 K, while we observed only a negative MR at elevated temperatures of 6 -10 K. The positive MR is attributed to the weak antilocalization (WAL) in the transport through the topological surface state (SS), demo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…And, given the valley degeneracy of SnTe, the coupling also likely comes from the scattering between two Dirac states on the same surface. The coupling between bulk and surface states has also been observed by Kuroda et al [ 51 ] who reported that both the numbers of transport channel and phase coherence length decrease with increase of temperature. This is because that thermal excited carriers take part in the transport and interact with the surface states at higher temperature.…”
Section: Quantum Coherence Transport Of Topological Surface Statessupporting
confidence: 62%
“…And, given the valley degeneracy of SnTe, the coupling also likely comes from the scattering between two Dirac states on the same surface. The coupling between bulk and surface states has also been observed by Kuroda et al [ 51 ] who reported that both the numbers of transport channel and phase coherence length decrease with increase of temperature. This is because that thermal excited carriers take part in the transport and interact with the surface states at higher temperature.…”
Section: Quantum Coherence Transport Of Topological Surface Statessupporting
confidence: 62%
“…The band inversion has been confirmed, and surface states have been observed, by angle-resolved photoemission spectroscopy (ARPES) [7,8]. Experimental evidence for topologically non-trivial surface states has been obtained in transport studies of thin films [9,10]. It has been proposed theoretically that combining topological surface states with bulk superconductivity may yield Majorana modes, which are of interest for use in quantum computing schemes [11,12].…”
Section: Introductionmentioning
confidence: 86%
“…Observations of WAL [39] in low-temperature magnetoresistance measurements on pristine SnTe have been used to identify the presence of topologically-protected surface states [9,10]. Recent theoretical work has demon- strated that one can also observe WAL from bulk Diraclike states with strong spin-orbit coupling [24].…”
Section: Magnetoresistancementioning
confidence: 99%
“…The MR curve at 5 K (black) clearly shows a cusp near zero field, which is a sign of the WAL effect and suggests the dominance of topological surface states. At elevated temperature, the cusp disappears, and the curves in the low-field regime (not shown) are dominated by the parabolic B-dependence of the bulk states [46,47], which is a reflection of the bulk carriers under a Lorentz force in a perpendicular field. The magnitude of the MR changes monotonically with temperature-a fact that needs further study to fully understand.…”
Section: Resistivity Behaviors Of In-doped Pb 1−x Sn X Tementioning
confidence: 99%